Biochemical properties and subcellular distribution of the neuronal class E calcium channel alpha 1 subunit - Yokoyama, CT (J Neurosci, 1995)
Anti-peptide antibodies specific for the neuronal calcium channel alpha 1E subunit (anti-CNE1 and anti-CNE2) were produced to study the biochemical properties and subcellular distribution of the alpha 1E polypeptide from rat brain. Immunoblotting identified a single size form of 245-255 kDa which was a substrate for phosphorylation by cAMP- dependent protein kinase, protein kinase C, cGMP-dependent protein kinase, and calcium/calmodulin-dependent protein kinase II. Ligand- binding studies of alpha 1E indicate that it is not a high affinity receptor for the dihydropyridine isradipine or the peptide toxins omega- conotoxin GVIA or omega-conotoxin MVIIC at concentrations which elicit high affinity binding to other channel types in the same membrane preparation. The alpha 1E subunit is widely distributed in the brain with the most prominent immunocytochemical staining in deep midline structures such as caudate-putamen, thalamus, hypothalamus, amygdala, cerebellum, and a variety of nuclei in the ventral midbrain and brainstem. Staining is primarily in the cell soma but is also prominent in the dendritic field of a discrete subset of neurons including the mitral cells of the olfactory bulb and the distal dendritic branches of the cerebellar Purkinje cells. Our observations indicate that the 245- 255 kDa alpha 1E subunit is localized in cell bodies, and in some cases in dendrites, of a broad range of central neurons and is potentially modulated by multiple second messenger-activated protein kinase.